Cardiac contractility modulation ameliorates myocardial metabolic remodeling in a rabbit model of chronic heart failure through activation of AMPK and PPAR-α pathway - Zhang Feifei; Liu Litian; Xie Yuetao; Wang Jiaqi; Chen Xuefeng; Zheng Shihang; Li Yingxiao; Dang Yi (Open Medicine, 2022)
Metabolic remodeling contributes to the pathological process of heart failure (HF). We explored the effects of cardiac contractility modulation (CCM) on myocardial metabolic remodeling in the rabbit model with HF. The HF in rabbit model was established by pressure uploading and then CCM was applied. We evaluated the cardiac structure and function by echocardiography, serum BNP level, and hematoxylin and eosin and Masson’s trichrome staining. We detected the accumulation of glycogen and lipid droplets in myocardial tissues by periodic acid-Schiff and Oil Red O staining. Then, we measured the contents of glucose, free fatty acid (FFA), lactic acid, pyruvate, and adenosine triphosphate (ATP) levels in myocardial tissues by corresponding kits and the expression levels of key factors related to myocardial substrate uptake and utilization by western blotting were analyzed. CCM significantly restored the cardiac structure and function in the rabbit model with HF. CCM therapy further decreased the accumulation of glycogen and lipid droplets. Furthermore, CCM reduced the contents of FFA, glucose, and lactic acid, and increased pyruvate and ATP levels in HF tissues. The protein expression levels related to myocardial substrate uptake and utilization were markedly improved with CCM treatment by further activating adenosine monophosphate-activated protein kinase and peroxisome proliferator-activated receptor-α signaling pathways.